การพัฒนาแบบวัดความฉลาดทางอารมณ์ สำหรับนักเรียนชั้นมัธยมศึกษาตอนปลาย - พรรณพร เรืองศรี (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
The purpose of this study was to develop the emotional intelligence scale for upper secondary school students. The scale was based on Goleman emotional intelligence concepts which composed of 5 factors awareness of self emotion, managing self emotions, motivating oneself, recognizing emotions of others and handling relationship with others. Likert scale with 3 degrees of opinion was applied. A sample of 1,084 were drawn by simple random sampling from upper secondary school students in Supanburi, Department of General Education, Ministry of Education. Item fit statistics were analyzed using BIGSTEPS program. The reliability of the scale was analyzed by using Cronbach ร alpha coefficient. The construct validity was detected through second order confirmatory factor analysis using LISREL program version 8.14. The results were as follows: 1. The emotional intelligence scale consisted 43 items with good fit statistics. 2. This was proved the reliability of the scale The Cronbach s coefficient value was 0.85. 3. This was proved the construct validity of the scale the second order confirmatory factor analysis indicated that the chi-square goodness of fit test of 1597.47, df = 801, GFI = 0.93, AGFI = 0.92.